Komposisi Jenis Kepiting Ocypodidae (Dekapoda: Brachyura) di Ekosistem Mangrove dan Estuari, TN Ujung Kulon - Dewi Citra Murniati (Universitas Atma Jaya Yogyakarta, 2010)
Mangrove and estuary ecosystems are important components of the intertidal area which is the habitat of Ocypodid crabs. The study of Ocypodid crabs in Ujung Kulon National Park is still limited, while its habitat is decreasing. This study was conducted to explore the Ocypodid crabs (Brachyura: Ocypodidae) composition in mangrove and estuary ecosystems in Ujung Kulon National Park. Crabs species collection was carried out in Legon Cibariang, Panaitan Island and Cikawung, Ujung Kulon National Park. Four species of Ocypodid crabs, Ocypode ceratophthalma (Pallas, 1772), Uca annulipes (H. Milne Edwards, 1837), U. coarctata (H. Milne Edwards, 1852) and U. triangularis (A. Milne Edwards, 1873) were successfully collected from mangrove and estuary ecosystems. The species composition of Ocypodidae in Cikawung were more various than in Legon Cibariang.